1992
DOI: 10.1042/bj2880351
|View full text |Cite
|
Sign up to set email alerts
|

Sustained activation of the mitogen-activated protein (MAP) kinase cascade may be required for differentiation of PC12 cells. Comparison of the effects of nerve growth factor and epidermal growth factor

Abstract: Stimulation of PC12 cells with nerve growth factor (NGF) increased mitogen-activated protein kinase kinase (MAPKK) activity > 20-fold after 5 min to a level that was largely sustained for at least 90 min. MAPKK activity was stimulated to a similar level by epidermal growth factor (EGF), but peaked at 2 min, declining thereafter and returning to basal levels after 60-90 min. Activation of MAPKK by either growth factor occurred prior to the activation of MAP kinase, consistent with MAPKK being the physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
651
3
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 871 publications
(689 citation statements)
references
References 20 publications
34
651
3
1
Order By: Relevance
“…These ®ndings suggest that di erences exist between the rapid stimulatory signal induced by EGF and the prolonged signalling mediated by constitutively active Cbl, Src, Ras and Raf. EGF stimulation is known to induce a rapid activation of MAP kinases which reaches a peak within 2 ± 5 min and returns to a basal level by 1 h (Buday and Downward, 1993b) whereas sustained activation is associated with translocation of MAP kinases to the nucleus (Traverse et al, 1992(Traverse et al, , 1994Nguyen et al, 1993;Dikic et al, 1994). In this study however we did not detect an increase in nuclear ERKs in 70Z-Cbl transformed cells (data not shown).…”
Section: Characterization Of Downstream E Ects Of 70z-cbl and V-cblcontrasting
confidence: 41%
“…These ®ndings suggest that di erences exist between the rapid stimulatory signal induced by EGF and the prolonged signalling mediated by constitutively active Cbl, Src, Ras and Raf. EGF stimulation is known to induce a rapid activation of MAP kinases which reaches a peak within 2 ± 5 min and returns to a basal level by 1 h (Buday and Downward, 1993b) whereas sustained activation is associated with translocation of MAP kinases to the nucleus (Traverse et al, 1992(Traverse et al, , 1994Nguyen et al, 1993;Dikic et al, 1994). In this study however we did not detect an increase in nuclear ERKs in 70Z-Cbl transformed cells (data not shown).…”
Section: Characterization Of Downstream E Ects Of 70z-cbl and V-cblcontrasting
confidence: 41%
“…Based on earlier published data we tested this possibility and found that dominant negative Rac1 completely blocked nuclear translocation of ERK1 by middle-T. This observation is not necessarily in contradiction to other reports showing that the activity of ERKs is independent of Rac1 (Minden et al, 1995;Coso et al, 1995; since phosphorylation of ERK by MEK is not su cient for nuclear translocation (Traverse et al, 1992).…”
Section: Discussionmentioning
confidence: 63%
“…In addition to a few differentially regulated genes with unknown function for the course of CDDP-induced apoptosis, we noted a sustained high level of MEK1/2 mRNA expression in NCCIT cells before and after drug treatment. MEK1 and MEK2 are protein kinases that when activated (phosphorylated) are believed to dually phosphorylate only ERK1 and ERK2, thereby increasing the enzymatic activity of ERKs approximately 1000-fold over the activity found with the basal or monophosphorylated forms (Traverse et al, 1992;Lenormand et al, 1993, Robbins et al, 1993. The consequence is a phosphorylation of diverse protein kinases, transcription factors, and even cytoskeletal proteins leading to paradoxical cellular responses ranging from proliferation to apoptosis (Peyssonnaux and Eychene, 2001;Djeu et al, 2002;Lee and McCubrey, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CDDP treatment resulted in high and sustained activation of MEK, particularly MEK1, and ERK, especially ERK2, which was strongly correlated to the apoptosis of tumour cells. Thus, it is tempting to speculate that a prolonged period of excessive phosphorylation of ERK may be necessary for its biological effect on TGCT as demonstrated for other cells types (Traverse et al, 1992;Lenormand et al, 1993).…”
Section: Discussionmentioning
confidence: 99%